Cancer survivors' and partners' key concerns and quality of life. Issue 11 (2nd November 2017) - Dorros, Sam M.; Segrin, Chris; Badger, Terry A.
Abstract : Objective: Understanding the concerns of cancer survivors is essential for effective interventions. This study was designed to identify the primary concerns of dyads coping with cancer, how concerns differed by role and sex, and whether concerns expressed during counselling were associated with survivors' psychosocial well-being and adjustment. Design: Forty-three dyads with breast and prostate cancer ( N  = 86 participants) were enrolled in an interpersonal telephone counselling intervention. Audio recordings of 228 counselling sessions were transcribed and content analysed qualitatively to identify major themes and key concerns. A total of three 30-min sessions were coded for each study participant. Quantitative data and statistical analyses were used to predict changes in survivors' quality of life. Main Outcome Measures: Participants completed psychosocial well-being measures (depression, positive/negative affect, and relationship satisfaction), pre- and post-counselling. Results: Survivors' concerns focused on cancer- and treatment-related issues, whereas partners' concerns centred on the well-being of their spouse/partner with cancer, and what they were doing to help their loved one cope with his/her illness. Key concerns for all consisted of relationship maintenance and communication issues. Further, discussion of these concerns was predictive of significant improvements in adjustment post-counselling for women with breast cancer. Conclusion: Discussion of interpersonal concerns may play a more important role in the well-being of women, than men, coping with cancer.